THE INFLUENCE OF GREEN INTELLECTUAL CAPITAL, GREEN INNOVATION, AND CARBON EMISSIONS DISCLOSURE ON FIRM VALUE WITH ENVIRONMENTAL PERFORMANCE AS A MODERATING VARIABLE - Marjuki; Nofryanti (ZILLZELL MEDIA PRIMA, 2025)
This research aims to investigate the impact of green intellectual capital, green innovation, and carbon emissions disclosure on firm value, and to explore whether environmental performance moderates this relationship. Using a sample of 156 data points from 52 energy and transportation companies’ observation the period trend 2023, the study employs panel data regression and moderated regression analysis to test the hypotheses. The findings reveal that green innovation has a positive influence on firm value. However, green intellectual capital and carbon emissions disclosure do not significantly impact firm value. Moreover, while environmental performance moderates the relationship between green intellectual capital and green innovation and firm value, it does not moderate the relationship between carbon emissions disclosure and firm value.